Analisis Mekanisme Bisnis E-Commerce melalui Transaksi Paylater dalam Perspektif Ekonomi Syariah: Studi Kasus Shopee Paylater - Deviniati; Imam Mawardi Imam (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2024)
E-commerce business is trending and gaining high popularity because it offers a lot of convenience in transactions. One of them is Shopee which is currently a very popular online shopping platform. The Shopee platform offers a variety of products and easy payment methods, including Shopee Paylater. Apart from the ease of using Shopee PayLater, Shopee users also need to be more aware of the risks of using Shopee PayLater. This research uses a qualitative method with a descriptive approach. Using two data sources, namely primary data obtained from interviews with Shopee users and Shopee Paylater customer service and secondary data from magazines, books, articles and websites about Shopee Paylater. The author uses inductive thinking in data analysis, starting from data and information on online business transactions via Shopee PayLater. The results of this research show that the Shopee PayLater loan application has terms and conditions that apply, including: Filling in the required personal data such as KTP and Emergency Contact completely and accurately. Shopee PayLater users are included in the qardh contract. However, in practice there are provisions that are not appropriate from a sharia economic perspective in accordance with the National Shariah Council of the Indonesian Ulema Council fatwa No: 116/DSN-MUI/IX/2017